Lifetime Prevalence and Correlates of Schizophrenia and Other Psychotic Disorders in Singapore - Subramaniam, Mythily; Abdin, Edimansyah; Vaingankar, Janhavi A.; Sambasivam, Rajeswari; Zhang, Yun Jue; Shafie, Saleha; Basu, Sutapa; Chan, Chun Ting; Tan, Chuen Seng; Verma, Swapna K.; Tang, Charmaine; Chua, Hong Choon; et al. (Frontiers in Psychiatry, 2021)
Introduction The current study aimed to establish the lifetime prevalence of schizophrenia and other psychotic disorders, its sociodemographic correlates and association with physical disorders using data from the Singapore Mental Health Study (SMHS 2016). Methods A two-phase design comprising population-level screening of psychotic symptoms using the World Health Organisation Composite International Diagnostic Interview version 3.0 psychosis screen followed by clinical reappraisal based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria was used to establish the prevalence. Results A total of 6,126 respondents completed the first phase of the study, giving a response rate of 69.5%. 5.2% (n=326) of respondents endorsed at least one symptom in the psychosis screen. After the phase two clinical reappraisal interviews and adjusting for false-negative rate, the corrected prevalence of schizophrenia and other psychotic disorders was 2.3% (95% CI: 2.3% to 2.3%). The odds of having DSM-IV schizophrenia and other psychotic disorders was significantly higher among those of Malay ethnicity (OR=3.9, 95% CI 1.4-11.0), and those who were unemployed (OR=4.3, 95% CI 1.2-15.9). 80.4% of those with a psychotic disorder had consulted a doctor or a mental health professional for their symptoms. Conclusions Our results indicate that approximately 2.3% of Singapore’s community-dwelling adult population had a lifetime diagnosis of schizophrenia and other psychotic disorders. While the treatment gap of the disorder was relatively small, the severe nature of the disorder emphasizes the need for continued outreach and early diagnosis and treatment.